2016
DOI: 10.1556/2060.103.2016.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of crocin and voluntary exercise against oxidative stress in the heart of high-fat diet-induced type 2 diabetic rats

Abstract: Background: Oxidative stress plays a critical role in the pathogenesis and progression of type 2 diabetes and diabeticassociated cardiovascular complications. This study investigated the impact of crocin combined with voluntary exercise on heart oxidative stress indicator in high-fat diet-induced type 2 diabetic rats. Materials and methods: Rats were divided into four groups: diabetes, diabetic-crocin, diabetic-voluntary exercise, diabetic-crocin-voluntary exercise. Type 2 diabetes was induced by high-fat diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…For example, voluntary physical activity has been shown to mitigate anxiety and depression-like behaviors and oxidative stress in a rat model of fetal alcohol spectrum disorders, 94 and to protect the heart from oxidative stress in diabetic rats. 95 As aforementioned, findings of the present study demonstrated similar anti-oxidative stress of Spirulina platensis at a dose of 200 mg/kg, voluntary exercise and enriched environment in rats submitted to chronic adolescent stress. Although the underlying mechanisms of anti-oxidative stress properties of these treatments are not known, they may interact with HPA axis, and thus, reduce oxidative stress.…”
Section: Discussionsupporting
confidence: 85%
“…For example, voluntary physical activity has been shown to mitigate anxiety and depression-like behaviors and oxidative stress in a rat model of fetal alcohol spectrum disorders, 94 and to protect the heart from oxidative stress in diabetic rats. 95 As aforementioned, findings of the present study demonstrated similar anti-oxidative stress of Spirulina platensis at a dose of 200 mg/kg, voluntary exercise and enriched environment in rats submitted to chronic adolescent stress. Although the underlying mechanisms of anti-oxidative stress properties of these treatments are not known, they may interact with HPA axis, and thus, reduce oxidative stress.…”
Section: Discussionsupporting
confidence: 85%
“…Crocin, namely crocetin esters, is one of the major pharmacological compounds in saffron [1, 5], possessing protective effect against cardiovascular diseases [1, 3, 5-7]. Data confirms that crocin improves cardiac function through partially reducing peroxidation damage [3, 8] or protecting myocardial cells against drug-induced cardiotoxicity [9, 10]. Crocin also exerts anti-atherosclerotic effects through the reduction of peroxide damage to endothelial cells [5, 11], and potently reduce mean arterial blood pressure in rats [7].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is not only associated with VD but is also associated with all risk factors for VD. Malondialdehyde (MDA) and superoxide dismutase (SOD) are widely used in many studies to represent the level of oxidative stress (26,27). MDA, a common marker for oxidative stress injury, is the product of lipid peroxidation in oxidative stress and is positively correlated with oxidative stress and lipid peroxidation (26).…”
Section: Discussionmentioning
confidence: 99%